2016
DOI: 10.1080/10408398.2015.1040113
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional role of free sialic acid, a human milk monosaccharide, and its application as a functional food ingredient

Abstract: N-Acetyl-d-neuraminic acid (NANA), more commonly known by its trivial name sialic acid, is an endogenous human and ubiquitous nutritional monosaccharide. As a bound sugar at the terminal positions of glycans NANA is known to play important roles in many biological events. The data that exist on the occurrence of the free monosaccharide in breast milk and nutrition, however, are less commonly discussed. In most foods of animal origin, sialic acid occurs as a mixture of NANA and N-glycolyl-d-neuraminic acid (NGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 289 publications
(156 reference statements)
2
44
0
2
Order By: Relevance
“…Other structure‐specific anti‐infective mechanisms have also been proposed (Kim et al, ). N ‐Acetyl and N ‐glycolyl forms of sialic acid represent a difference in structure that inevitably contributes towards fighting infection and providing nutrition (Röhrig, Choi, & Baldwin, ), but these are not the only attributes being considered. The specificity between the 3′‐ and 6′‐isomers may also be vital to the recognition of serious pathogens such as the human influenza A/B viruses (Gagneux et al, ), and 3′‐SL has recently been reported to show preventive effects on rheumatoid and osteoarthritis in vitro and in mouse models (Jeon et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other structure‐specific anti‐infective mechanisms have also been proposed (Kim et al, ). N ‐Acetyl and N ‐glycolyl forms of sialic acid represent a difference in structure that inevitably contributes towards fighting infection and providing nutrition (Röhrig, Choi, & Baldwin, ), but these are not the only attributes being considered. The specificity between the 3′‐ and 6′‐isomers may also be vital to the recognition of serious pathogens such as the human influenza A/B viruses (Gagneux et al, ), and 3′‐SL has recently been reported to show preventive effects on rheumatoid and osteoarthritis in vitro and in mouse models (Jeon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other structure-specific anti-infective mechanisms have also been proposed (Kim et al, 2019). N-Acetyl and N-glycolyl forms of sialic acid represent a difference in structure that inevitably contributes towards fighting infection and providing nutrition (Röhrig, Choi, & Baldwin, 2017), but these are not the only attributes being considered.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, freely occurring sialyllactoses have been confirmed to interfere with receptor binding of many of these pathogens (Laucirica, Triantis, Schoemaker, Estes, & Ramani, 2017;Marotta, Ryan, & Hickey, 2014). It is not only the subtle structural difference between the N-acetyl and N-glycolyl forms of sialic acid that plays an important role in the context of infection and nutrition (Röhrig, Choi, & Baldwin, 2017), but the difference between the 3′-and 6′isomers with a confirmed human upregulation of 6′-linked sialic acids being possibly linked to the evasion of critical pathogens such as influenza is also a contributing factor (Gagneux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the gut, sialic acid prevents the adhesion of pathogens and promotes the growth of Bifidobacteria (Egan, Motherway, Ventura, & van Sinderen, 2014). From a nutritional point of view, sialic acid is crucial for immune and cognitive development (Röhrig, Choi, & Baldwin, 2017). However, the presence of some glycans, such as the Gal (α1-3)Gal epitope present in bovine glycoproteins and not in HMGPs, have been linked with undesirable effects, such as allergic reactions (Rispens, Derksen, Commins, Platts-Mills, & Aalberse, 2013).…”
Section: Hmgps Concentration (G/dl)mentioning
confidence: 99%